Point Prevalence Survey of Nosocomial Infections in University Hospital in Martin - Malobicka E; Roskova D; Svihrova V; Hudeckova H. (Acta Medica Martiniana, 2013)
Nosocomial infections are a serious problem not only in Slovakia but in all countries. The European Commission decided on their standardized surveillance in the whole European Union. According methodology elaborated by experts from the European Centre for Disease Control and Prevention in Stockholm we performed a point prevalence survey in the University Hospital Martin.